Exploring challenges in designing and implementing internal control systems: A case study of small and medium enterprises in the Cape Metropole, South Africa - Musikavanhu, Tichaona; Nqala, Lisa (Universitas Nahdlatul Ulama Surabaya, 2024)
Small and medium enterprises (SMEs) are pivotal in bolstering a country’s economy, particularly in South Africa, where high unemployment persists. In this context, studying SMEs’ survival becomes paramount as a potential remedy for alleviating economic poverty. Effective internal control systems emerge as crucial tools in this endeavour, serving slot gacor 777 as key mechanisms for risk management. They are instrumental in preventing fraud, safeguarding company assets, and ensuring the longevity and resilience of SMEs in challenging economic landscapes. Many SMEs design and implement internal control systems as a formality without fully considering their strategic objectives and potential impact on business operations. This research aimed to understand the challenges associated with designing and implementing effective internal control systems within SMEs in the Cape Metropole, South Africa. The study used a qualitative research methodology to collect data through interviews and employ thematic analysis for interpretation. The findings of this study shed light on the significant challenges faced by SMEs) in the Cape Metropole, South Africa when it comes to designing and implementing effective internal control systems. These challenges highlight the limitations of the existing internal control systems within SMEs, particularly their capacity to fulfil crucial business objectives. Furthermore, this paper highlights a notable gap in SMEs’ comprehension and application of internal control systems, highlighting the need for effective, efficient, and tailored internal control systems to meet their unique business requirements.